Elaboración de un plan estratégico para la empresa servirepuestos Beto de la ciudad de Loja - Merino Chiriboga, Carla Gabriela (2016)
This research has the general objective perform PROPOSAL OF A STRATEGIC PLAN FOR THE COMPANY SERVIREPUESTOS BETO de Loja, with which it aims to improve and renew the internal processes of the Commercial, within this Plan will be determined and processes missing requirements within the company, which is engaged in the distribution and marketing of auto parts and accessories for all makes and models. The development of this project was made in a systematic manner, complying with all the parameters established in the legislation of the National University of Loja, where all matters related to the strategic planning and how it will implement this plan addresses inside the company. The methods used for the implementation of this research are: Analytical Method; enabling discover the different elements of the nature or essence of the research problem, historical method; which it was used to examine the path of Commercial SERVIREPUESTOS BETO since its inception to date, Inductive Method; that is applied to analyze the issues raised and structure proposed in this study, descriptive method objectives; Used to describe the process and collected field information and then be able to obtain the results and conclusions. Statistical method; which serves to tabular data obtained from surveys and interviews. The techniques used in this research were observation, interview and survey. Also in this research, we proceeded to perform external analysis, where the following factors are considered: Economic, Political, Social, Technological, Environmental, whose realization was reached to obtain the information necessary to produce the EFE matrix (matrix evaluation external) factors, the same result provided a weighted value of 2.79 indicates that there BETO SERVIREPUESOS Commercial opportunities dominance. Similarly we proceeded to the analysis of internal factors, for that 388 surveys were applied to external customers, internal customers 7 polls and interview Mr. Edilberto Merino, Manager of Commercial study; information obtained through the completion of the analysis of internal factors formed the basis for the development of the EFI matrix (matrix evaluation of internal factors), the result was 2.72 weighted indicator which shows that this company is consolidated internally. Collection of information obtained through the completion of the analysis of external and internal factors, we proceeded to the development of the SWOT matrix, which encompasses within its organizational structure to major Strengths, Weaknesses, Opportunities and Threats SERVIREPUESTOS characterizes BETO. The development of the SWOT matrix was formed in the previous step which facilitated the structuring of High Impact matrix; and conjugation technique crosses DO- FO- FA DA, they came to achieve strategic objectives for the Trade; these strategic objectives came to constitute the fundamental part of this Strategic Plan, whose structure is based on the determination of a goal, strategy, policy, activities, time, budget and responsible for compliance, and which were the strategic objectives. Finally culminating in the structuring of the respective conclusions andrecommendations, which are proposed to the manager of this company is fulfilled's proposal designed for commercial SERVIREPUESTOS BETO Strategic Plan, whose budget is $ 3.314.39 (THREE THOUSAND HUNDRED FOURTEEN )